Marital status and paternity in patients with Transfusion- Dependent Thalassemia (TDT) and Non Transfusion-Dependent Thalassemia (NTDT): an ICET - A survey in different countries - De Sanctis, Vincenzo; Soliman, Ashraf T; El-Hakim, Ihab; Christou, Soteroula; Mariannis, Demetris; Karimi, Mehran; Ladis, Vassilis; Kattamis, Antonis; Daar, Shahina; Yassin, Mohamed; Canatan, Duran; Galati, Maria Concetta; et al. (Acta Biomedica Atenei Parmensis, 2019)
Background: More than five decades ago, thalassemia major (TDT) was fatal in the first decade of life. Survival and quality of life have improved progressively thanks to the implementation of a significant advance in diagnostic and therapeutic methods, consisting mainly of a frequent transfusion program combined with intensive chelation therapy. Improvement also includes imaging methods used to measure liver and cardiac iron overload. Improved survival has led to a growing number of adults requiring specialised care and counselling for specific life events, such as sexual maturity and acquisition of a family. Aims of the study: The main aim is to present the results of a survey on the marital and paternity status in a large population of adult males with TDT and NTDT living in countries with a high prevalence of thalassemia and a review of current literature using a systematic search for published studies. Results: Ten out of 16 Thalassemia Centres (62.5%) of the ICET-A Network, treating a total of 966 male patients, aged above 18 years with β- thalassemias (738 TDT and 228 NTDT), participated in the study. Of the 966 patients, 240 (24.8%) were married or lived with partners, and 726 (75.2%) unmarried. The mean age at marriage was 29.7 ± 0.3 years. Of 240 patients, 184 (76.6%) had children within the first two years of marriage (2.1 ± 0.1 years, median 2 years, range 1.8 - 2.3 years). The average number of children was 1.32 ± 0.06 (1.27 ± 0.07 in TDT patients and 1.47 ± 0.15 in NTDT patients; p: >0.05). Whatever the modality of conception, 184 patients (76.6%) had one or two children and 1 NTDT patient had 6 children. Nine (4.8%) births were twins. Of 184 patients, 150 (81.5%) had natural conception, 23 (12.5%) required induction of spermatogenesis with gonadotropins (hCG and hMG), 8 (4.3%) needed intracytoplasmic sperm injection (ICSI) and 3 adopted a child. 39 patients with TDT and NTDT asked for medical help as they were unable to father naturally: 7 TDT patients (17.9%) were azoospermic, 17 (37.7%) [13 with TDT and 4 with NTDT] had dysspermia and 15 (33.3%) [13 with TDT and 2 with NTDT] had other “general medical and non-medical conditions”. Conclusions: Our study provides detailed information in a novel area where there are few contemporary data. Understanding the aspects of male reproductive health is important for physicians involved in the care of men with thalassemias to convey the message that prospects for fatherhood are potentially good due to progressive improvements in treatment regimens and supportive care.